Penerapan Prinsip-Prinsip Hukum Islam Dalam Pembuatan Undang-Undang Di Indonesia - Rasyid, M.Ag, Dr. Muh. Haras; Herawati, Andi (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2023)
As the title of this research, it emphasizes the study of the flexibility of Islamic law in giving a role to the issue of the process of forming legislation in Indonesia. Because the problem that always arises is the dissatisfaction of some people with every law product made by the executive and legislative branches. Therefore, by applying the principles of Islamic law to every lawmaking process, it is possible to minimize public disapproval of every law product. This paper is studied in accordance with reality by analyzing sociological, philosophical and juridical approaches which aim that every existing law can be applied effectively and sustainably in accordance with the ideological and philosophical foundations of the Indonesian nation.